The Use of Learning Media "Fun Physics Learning” Based on Android to Improve Problem-Solving Skills of Students - Atika Diah Isnaeni Putri; Rahmat Firman Septiyanto; Asep Saefullah (JURNAL EKSAKTA PENDIDIKAN (JEP), 2023)
The research is motivated by the low problem-solving skills of students in learning physics. This study aims to determine whether there is no increase in the effectiveness of using Android-based learning media “Fun Physics Learning” on students' problem-solving skills. This type of research used a quasi-experimental design with a non-equivalent control group design. The population used was all students of class X SMAS Mandiri Balaraja, while the research sample used two classes, class X for the experimental class and the control class. The instrument used is a test in the form of an essay, which the validator and student response sheets have validated to the Physics Scatter application. Data analysis showed that there was a significant increase in the results of students' problem-solving skills, which were shown in the pretest and post-test of the experimental class, where there was a significant increase in the N-Gain acquisition of 0.61 in the medium category. Based on the hypothesis test using the t-independent sample test, obtained t-count = 11.002 and t-table = 2.045 at a significant level of 0.05 and got a positive student response. It was concluded that using Android-based Physics Spread learning media can improve students' problem-solving skills and is effectively used in learning.